Federal Rules of Appellate Procedure - eLangdell Press, Editorial Staff, author (Open Textbook Library, 2016)
The Federal Rules of Appellate Procedure appear in the Appendix to Title 28 of the United State Code.
Chapter 1: Applicability of Ruiles Chapter 2: Appeal From a Judgment or Order of a District Court Chapter 3: Review of a Decision of the United States Tax Court Chapter 4: Review or Enforcement of an Order of an Administrative Agency, Board, Commission, or Officer Chapter 5: Extraordinary Writs Chapter 6: Habeas Corpus; Proceedngs in Forma Pauperis Chapter 7: General Provisions
The Federal Rules of Appellate Procedure appear in the Appendix to Title 28 of the United State Code. This publication was made with data provided by the United States government on the Office of Law Revision Counsel Bulk US Code. This title is current through July 31, 2014.  All updates to this material will appear at the above URL.
Keywords: law